![\frac{7y + 3}{y - 2} = \frac{4}{3} \frac{7y + 3}{y - 2} = \frac{4}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7B7y+%2B+3%7D%7By+-+2%7D+%3D++%5Cfrac%7B4%7D%7B3%7D+)
Attachments:
![](https://hi-static.z-dn.net/files/d5d/92957b116a06bdbf7c1ff9ea429a1d91.jpg)
Answers
Answered by
0
Answer:
please see attached file and you will get answer
Attachments:
![](https://hi-static.z-dn.net/files/d9c/d46907880c57bcc086cc2db27118045f.jpg)
Answered by
0
Answer:
3y+9=4y-8
+9+8=4y-3y
+17=y
Step-by-step explanation:
THUS,Y =17
VERIFICATION-
17+3/17-2=20/15=4/3.
Similar questions
English,
1 month ago
Math,
1 month ago
Computer Science,
2 months ago
English,
9 months ago
Hindi,
9 months ago